Comparison between Needle Aspiration and Chest Tube Drainage in the Management of Primary Spontaneous Pneumothorax - Bushra Tasneem, Muhammad Aamir Alsabah, Aijaz Ahmed Laghari, Aisha Tasneem, Agha Taj Mohammad, Rasool Bux Behan (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To compare the effectiveness of needle aspiration and chest tube drainage in the management of primary spontaneous pneumothorax Subject and Methods: A Total of 58 patients of primary spontaneous pneumothorax PSP were divided into two groups as per management modality. Group A was treated with needle aspiration NA and group B was managed with chest tube drainage CTD. Frequency of gender and current smoker was noted. Mean and standard deviation was calculated for age and body mass index BMI. Clinical characteristics like hospitalization days, immediate and 1 week success rate and recurrence was noted on proforma. Frequency of minor postoperative complication was observed for both groups. Results: The majority of patients were males in both groups. Mean age of patients was 47.29 ± 5.68 for NA group and 49.28 ± 6.25 for CTD group. Immediate and 1 week success rate was 17 (58.6%) 27 (93.1%) for NA group, while in CTD group it was 22 (75.86%) and 28 (96.5%) respectively. Mean hospitalization time for NA group was 1.42±0.38, and for CTD it was 4.62±1.12. 1 year recurrence rate was higher in NA group than the CTD group. Conclusion: Considering its advantages, NA was recommended as first line management in the patients of PSP.